2023
DOI: 10.1007/s10489-022-04427-x
|View full text |Cite
|
Sign up to set email alerts
|

Classification framework for faulty-software using enhanced exploratory whale optimizer-based feature selection scheme and random forest ensemble learning

Abstract: Software Fault Prediction (SFP) is an important process to detect the faulty components of the software to detect faulty classes or faulty modules early in the software development life cycle. In this paper, a machine learning framework is proposed for SFP. Initially, pre-processing and re-sampling techniques are applied to make the SFP datasets ready to be used by ML techniques. Thereafter seven classifiers are compared, namely K-Nearest Neighbors (KNN), Naive Bayes (NB), Linear Discriminant Analysis (LDA), L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 98 publications
0
17
0
Order By: Relevance
“…The results of the experiments showed that the proposed nestedstacking system outperformed the baseline models. In [15], the researchers proposed a framework based on the Binary Whale Optimization Algorithm (BWOA) called SBEWOA. The BWOA was used as an FS method that utilized transfer functions to convert the original continuous WOA into a binary version suitable for FS.…”
Section: A Rq1: Which Feature Selection Methods Are Implemented For S...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the experiments showed that the proposed nestedstacking system outperformed the baseline models. In [15], the researchers proposed a framework based on the Binary Whale Optimization Algorithm (BWOA) called SBEWOA. The BWOA was used as an FS method that utilized transfer functions to convert the original continuous WOA into a binary version suitable for FS.…”
Section: A Rq1: Which Feature Selection Methods Are Implemented For S...mentioning
confidence: 99%
“…In recent years, feature selection methods have gained more prominence due to their capability to enhance prediction accuracy and reduce model creation time [15]- [19]. These methods find applications in various domains, including healthcare and medicine, fraud detection, sentiment analysis, etc.…”
Section: Introductionmentioning
confidence: 99%
“…A classification framework 35 is designed to identify faulty software efficiently. The approach is characterized by the integration of two key components: an enhanced exploratory Whale Optimization Algorithm (WOA) for feature selection and a Random Forest ensemble learning model for classification.…”
Section: In-depth Review Of Existing Machine Learning Models Used For...mentioning
confidence: 99%
“…For detecting and classifying the CKD, the AGRU model can be used. RNN is a network persisting data for sequence-related tasks [20]. But, RNN suffers from short-term memory.…”
Section: Classification Using Agru Modelmentioning
confidence: 99%